A numeric-based machine learning design for detecting organized retail fraud in digital marketplaces - Mutemi, Abed (2023)
Mutemi, A., & Bacao, F. (2023). A numeric-based machine learning design for detecting organized retail fraud in digital marketplaces. Scientific Reports, 13(1), 1-16. [12499]. https://doi.org/10.1038/s41598-023-38304-5